2015
DOI: 10.1088/0004-637x/806/2/176
|View full text |Cite
|
Sign up to set email alerts
|

Measuring an Eruptive Prominence at Large Distances From the Sun. Ii. Approaching 1 Au

Abstract: The physical properties of eruptive prominences are unknown at large distances from the Sun. They are rarely, if ever, measured by in situ spacecraft and until recently our ability to measure them beyond the fields of view of solar imagers has been severely limited. The data quality of heliospheric imaging has reached a point where some quantitative measurements of prominences are now possible. I present the first such measurements of a bright prominence continually out to distances of around 1 AU from the Sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
(34 reference statements)
3
15
0
Order By: Relevance
“…They found that filaments are not necessarily tied to the magnetic properties of their accompanying CME and that the geometry of the filaments remained intact out to many tens of R e . The two filaments studied by Howard (2015aHoward ( , 2015b and Wood et al (2016) were clear cases of CME cores that were actual filaments that originated at the Sun and propagated through the heliosphere. Although additional such filaments were sought by Wood et al (2016) they found only those two in the STEREO/ HI-2 data sets for the entire duration of the STEREO mission.…”
Section: Recent Work On Filaments At Large Distances From the Sunmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that filaments are not necessarily tied to the magnetic properties of their accompanying CME and that the geometry of the filaments remained intact out to many tens of R e . The two filaments studied by Howard (2015aHoward ( , 2015b and Wood et al (2016) were clear cases of CME cores that were actual filaments that originated at the Sun and propagated through the heliosphere. Although additional such filaments were sought by Wood et al (2016) they found only those two in the STEREO/ HI-2 data sets for the entire duration of the STEREO mission.…”
Section: Recent Work On Filaments At Large Distances From the Sunmentioning
confidence: 99%
“…Of those, only two have so far been confirmed to contain eruptive filaments that have been tracked to large distances from the Sun. These were associated with CMEs that departed the Sun on 2011 June 07 and 2012 August 31 and the large-distance evolution of both have been investigated by Howard (2015aHoward ( , 2015b and Wood et al (2016). A summary of these works is provided in Section 1.1.…”
Section: Do Any Filaments Survive Far From the Sun?mentioning
confidence: 99%
“…Some CME parameters assumed in this study can be derived from LASCO white-light images by tting the CME geometry using models such as the graduated cylindrical shell model (e.g., Thernisien et al 2006). CMEs propagating in interplanetary space can be derived from the Heliospheric Imager onboard STEREO satellites (Möstl et al 2014;Howard 2015). White-light coronagraph data can also be estimated from our MHD simulations by calculating the Thomson scattering along the line of sight.…”
Section: Causes Of the Arrival-time Errormentioning
confidence: 99%
“…Under this narrative, the shock and sheath in-situ components correspond to the bright leading edge in the coronagraph three-part CME, but the fate of the underlying filament component observed in coronagraphs remains open to debate. Little evidence exists of filament signatures at large distances from the Sun (Howard 2015b), and although periods of high-density cold plasma have been observed in-situ (e.g., Cane et al 1986;Yao et al 2010) it remains an open question as to whether these features are actually filaments and therefore how commonplace they are within CMEs at distances near 1 AU.…”
Section: A Brief Review Of the History Of Cme Observationmentioning
confidence: 99%
“…4.2) they concluded that the light was due to Ha emission, as photospheric Ha is known to have an unusually low polarization due to Lyb absorption . The author has recently published two papers that explore a filament measured at large distances from the Sun (Howard 2015a(Howard , 2015b. …”
Section: The Thomson Scattering Assumptionmentioning
confidence: 99%